Isotropic 25-Micron 3D Neuroimaging Using ex vivo Microstructural Manganese-Enhanced MRI (MEMRI) - Sato, Chika; Sawada, Kazuhiko; Wright, David; Higashi, Tatsuya; Aoki, Ichio (Frontiers in Neural Circuits, 2018)
MRI observations following in vivo administration of Mn2+ [manganese (Mn)-enhanced MRI, MEMRI] have been used as an excellent morphological and functional MRI tool for in vivo preclinical studies. To detect brain three-dimensional (3D) microstructures, we improved the ex vivo MEMRI method for mouse brains after in vivo Mn administration and obtained high-resolution MRIs using a cryogenic radiofrequency (RF) coil. Male C57BL/6 mice (n = 8) were injected with 50 mM MnCl2 intravenously and MEMRIs of the brain were acquired in vivo after 24 h, followed by perfusion fixation with a 4% paraformaldehyde (PFA) solution. High-resolution 25-μm isotropic MRIs were successfully acquired from the extracted brain tissue and could identify the brain microstructures, especially in the hippocampus [the pyramidal cell layer through CA1–3 and the dentate gyrus (DG) granular layers (GLs)], cell layers of cerebellum, three sub-regions of the deep cerebellar nucleus, and white matter (WM) structures [e.g., the fasciculus retroflexus (fr) and optic tract in the thalamus]. The following technical conditions were also examined: (i) the longitudinal stability of Mn-enhanced ex vivo tissue after in vivo administration; and (ii) the effects of mixing glutaraldehyde (GA) with the fixative solution for the preservation of in vivo MEMRI contrast. Our results indicate that ex vivo MEMRI observations made shortly after fixation maintain the contrast observed in vivo. This research will be useful for non-destructive whole-brain pathological analysis.